2018
DOI: 10.1186/s12891-018-2358-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of oral compared with intravenous tranexamic acid in reducing blood loss after primary total knee and hip arthroplasty: a meta-analysis

Abstract: BackgroundTranexamic acid (TXA) is an anti-fibrinolytic agent successfully preventing blood loss when using intravenously (IV) in total hip arthroplasty (THA) and total knee arthroplasty (TKA). An oral administration, which is available on blood sparing, has been reported exhibit profound cost-saving benefits. The aim of this meta-analysis is to investigate whether the administration of oral and intravenous tranexamic acid postoperatively has equivalent blood-sparing properties in these patients.MethodsThe onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In cases of arthroplasty, tranexamic acid does not significantly increase the rate of deep venous thrombosis or pulmonary embolism. [ 4 , 15 , 17 ]. However, there is uncertainty regarding the effect of tranexamic acid on the incidence of thromboembolism in case of surgical bleeding [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of arthroplasty, tranexamic acid does not significantly increase the rate of deep venous thrombosis or pulmonary embolism. [ 4 , 15 , 17 ]. However, there is uncertainty regarding the effect of tranexamic acid on the incidence of thromboembolism in case of surgical bleeding [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies have been used to minimize blood loss and to avoid blood transfusion, which may cause adverse effects, such as infection and transfusion reactions [1,3]. In this regard, pre-and postoperative administration of tranexamic acid has been effective [13][14][15]. However, its use is contraindicated in patients with a history of thromboembolism, and is associated with adverse events, such as allergies [16].…”
Section: Discussionmentioning
confidence: 99%
“…They all concluded that TXA was effective after THA/TKA. Grandhi et al [37], Wei et al [14], Dong et al [38], and Kuo et al [39] conducted meta-analyses to evaluate the effectiveness and safety of aminocaproic acid for reducing blood loss in total knee and hip arthroplasty; Li et al [40], Chen et al [41] and Yang et al [42] conducted meta-analyses to comprise the efficacy and safety of topical, system and intravenous tranexamic acid usage in total knee and hip arthroplasty; Zhang et al [43] and Han et al [44] conducted meta-analyses to compared the efficacy and safety of oral compared with intravenous tranexamic acid in reducing blood loss after primary total knee and hip arthroplasty. However, they only focused on the administration of TXA itself, but did not analysed other influencing factors.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Thomas [23] indicated that shed autologous blood reinfusion could significantly reduce the demand for allogeneic blood, but on average, the medical cost for each patient was increased by 113 pounds. On the contrary, a meta analysis by Han et al[24] demonstrated that the application of tranexamic acid has blood-sparing and cost-benefit properties in theses patients. Unfortunately, tranexamic acid was not used in the three hospitals above because of clinical habit which was verified the efficacy of blood sparing.…”
Section: Discussionmentioning
confidence: 99%